Mechanical Property Change in the Region of Very High-cycle Fatigue. (2015) - Xiong, Zhihong; Naoe, Takashi; Wan, Tao; Futakawa, Masatoshi; Maekawa, Katsuhiro
Abstract: Very high-cycle fatigue behaviour of type 316L austenitic stainless steel, which is used as the structural material of the pulsed spallation neutron sources, was investigated through the ultrasonic fatigue test with the strain rate of 10 2 1/s. Cross-sectional hardness distributions of the fatigue-failed specimens for solution annealed (SA) and cold worked (CW) 316L were measured to understand the cyclic hardening or softening in the very high-cycle fatigue region. In addition, the tensile tests of the fatigue-failed specimens were performed at room temperature. Furthermore, the nonlinear ultrasonic system was used for evaluating the dislocation density variation during plastic deformation. The results showed the cyclic hardening in the region of very high-cycle fatigue in the case of SA 316L. In contrast, in the case of 10% CW 316L, cyclic softening occurred when the number of cycles below 10 6 and followed by cyclic hardening. In the case of 20% CW 316L, cyclic softening was observed when the number of cycles below 10 7, while cyclic hardening occurred subsequently.